Obtaining diesel fuels with improved low temperature properties by adding petroleum resins, n-paraffins and a depressant; Химия и химическая технология в XXI веке; Т. 2 - Orlova A. M. Anna Markovna (Химия и химическая технология на иностранном языке (английский), 2022)
Заглавие с титульного экрана